Penerapan Inovasi Media Zeoponik Berbasis Zeolit untuk Peningkatan Kualitas Pembibitan Tanaman Hortikultura di Kecamatan Mojosongo, Boyolali - Suwardi; Dyah Tjahyandari Suryaningtyas1; Putri Oktariani; Hermanu Widjaja; Octaviana Randrikasari (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
The "Dosen Pulang Kampung" (Lecturer Goes Home) program is a community service effort conducted by IPB University aimed at contributing knowledge and technology to rural communities. In this activity, the authors introduced Zeoponic planting media to horticultural farmers in Mojosongo District, Boyolali. Zeoponic, a zeolite-based planting medium, is designed to address the high electrical conductivity (EC) problems in traditional planting media, which often hinder nutrient absorption. With zeolite content, Zeoponic has a high cation exchange capacity (CEC), maintaining EC and moisture stability, thus supporting optimal seedling growth. The activity was carried out in three stages: a theoretical session explaining the concept and benefits of the medium, a demonstration of its preparation directly by the farmers, and an evaluation through discussions as well as pre-test and post-test to assess participants’ knowledge improvement. A total of 30 farmers from local farmer groups in Mojosongo participated in the program. Results showed that Zeoponic could improve the quality of horticultural plant seedlings and has great potential for adoption by local farmers. This program is expected to support sustainable agriculture and enhance the welfare of farmers.